The Wills eye manual office and emergency room diagnosis and treatment of eye disease - Gervasio, Kalla A.; Peck, Travis J.; Fathy, Cherie A.; Sivalingam, Meera D.; Friedberg, Mark A.; Rapuano, Christopher J. (Wolters Kluwer, 2022)
"A best-selling source of compact, authoritative guidance on the treatment of ocular disorders in a variety of settings, The Wills Eye Manual, 8th Edition, is the comprehensive, high-yield reference of choice for both trainees and seasoned practitioners. It provides highly illustrated information on more than 200 ophthalmic conditions along with proven clinical recommendations from initial diagnosis through extended treatment. The consistent, bulleted outline format makes it ideal for portability and quick reference. Provides current, superbly illustrated information on more than 200 ophthalmic conditions in a handy, portable manual, along with extensive multimedia content. Features easily accessible clinical recommendations for evaluation, diagnosis, management, and treatment. Contains updates on the latest major clinical trials in ophthalmology, as well as two expertly produced new videos and many new clinical images added. Addresses changing trends in oculoplastics, glaucoma, cornea, pediatrics, neuro-ophthalmology, uveitis, retina, and more. Includes videos depicting a wide range of common procedures with step-by-step narration, carefully selected to complement key techniques. All chapters written and edited by the residents and attending ophthalmologists at one of the busiest and largest eye hospitals in the country"--